P195 Prospective Examination Of The Effects Of Ivacaftor On Glycaemic Health. (10th November 2014) - Banerjee, A; Brennan, AL; Horsley, AR; Barry, PJ
Abstract : Background: The clinical benefits of the novel cystic fibrosis transmembrane conductance regulator (CFTR) have now been well established for patients carrying the G551D mutation through both phase 3 and real world clinical studies. Modulation of CFTR alters intestinal pH, which may assist in the function of pancreatic enzymes and which theoretically might have an impact on the absorption of nutrients in cystic fibrosis (CF). This may have significant impact on the glycaemic health of patients and early reports from a phase 2 study suggested a significant risk of hyperglycaemia in a patient with pre-existing diabetes. Aim: We aimed to prospectively assess the impact of ivacaftor on glycaemic health Methods: We conducted a prospective observational cohort study of subjects who commenced ivacaftor following NHS approval. Baseline measures were recorded including spirometric measures, weight and sweat chloride. Glycaemic control was assessed using HbA1c and repeated measures were recorded at 1, 3 and 6 months. Results: 24 subjects were included in the study. 17 subjects had normal glucose handling as defined by oral glucose tolerance test, 4 subjects had a pre-existing diagnosis of CF-related diabetes and 3 subjects had impaired glucose tolerance prior to ivacaftor commencement. Ivacaftor significantly increased FEV1 and BMI at 1, 3 and 6 months compared to baseline, and decreased sweat chloride at 2 months, all indicating effective CFTR modulation. There was a significant reduction in HbA1c from baseline to 6 months in the total cohort, (median 42.5 mmol/L versus 39.5 mmol/L, p = 0.004), but not at other time points. In the diabetic or IGT subgroups, there were no clinically significant changes in HbA1c. Conclusion: Ivacaftor is an effective treatment for CF patients carrying the G551D mutation. In normoglycaemic patients, Ivacaftor significantly reduces HbA1c at 6 months. There was no adverse effect on glucose control noted in diabetic or impaired glucose tolerance subgroups. This may be attributable to improved insulin secretion by CFTR related mechanisms or improved insulin sensitivity. These results are important and re-assuring when commencing patients with diabetes on CFTR modulators.